AGRO-ECONOMIC DEVELOPMENT BASED ON THE ECONOMY OF KNOWLEDGE, BUSINESS AND SOCIAL SKILLS - Cukanovic-Karavidic, Marija; Karavidić, Slavko; Pejanović, Radovan (Economics of Agriculture, 2018)
In this paper, we tried to point out the contemporary global trends of agrarian development that generate new knowledge, a new way of learning, new innovative and creative techniques of professional training - business and social skills. Intention is to provide support and encouragement to enter new forms of agrarian business. Since education, as a dominant need for agrarian research, is in the function of labor or occupation, we wanted to provide an insight into the educational needs required for professional education and training, as well as how much the content of work in the agrarian defines educational needs and expresses interest in vocational education and training, by affirming practice through the realm of work and business results.